Crosstalk between T cells and fibroblasts in biomaterial-mediated fibrosis - Mathew Kibet; Daniel Abebayehu (Matrix Biology Plus)
Biomaterial implants are a critical aspect of our medical therapies and biomedical research and come in various forms: stents, implantable glucose sensors, orthopedic implants, silicone implants, drug delivery systems, and tissue engineered scaffolds. Their implantation triggers a series of biological responses that often times lead to the foreign body response and subsequent fibrotic encapsulation, a dense ECM-rich capsule that isolates the biomaterial and renders it ineffective. These responses lead to the failure of biomaterials and is a major hurdle to overcome and in promoting their success. Much attention has been given to macrophage populations for the inflammatory component of these responses to biomaterials but recent work has identified an important role of T cells and their ability to modulate fibroblast activity and vice versa. In this review, we focus on T cell-fibroblast crosstalk by exploring T cell subsets, critical signaling pathways, and fibroblast populations that have been shown to dictate biomaterial-mediated fibrosis. We then highlight emerging technologies and model systems that enable new insights and avenues to T cell-fibroblast crosstalk that will improve biomaterial outcomes.